Isolation And Characterization Of Psychrotolerant Paenibacillus Agaridevorans Strain S26 From Subglacial Himalayan Lake - S. VARDHAN,; A.K. YADAV,; S. KASHYAP,; A. K. PANDAY,; A.K. SRIVASTAVA,; D.K. ARORA, (International Journal of Pharma and Bio Sciences, 2012)
Pangong Lake is the largest brackish snow capped lake in the subglacial Himalayan region of India. A psychrophillic Paenibacillus agaridevorans strain 26, producing a cold-adapted lipase with the specific activities of 7.894 U/mg and 0.163 U/mg at the temperature of 10 and 20 °C at 7th day respectively. First representative of this species were isolated from volcanic rock soil of Paricutin, Mexico and we are reporting bacteria from psychrophillic environment of India. Taxonomic characterization and identification of Paenibacillus agaridevorans-S26 was carried out using polyphasic approaches including morphological, physiological and molecular approaches by 16S rDNA sequencing (Accession number HQ290361).